2022
DOI: 10.3390/s22197686
|View full text |Cite
|
Sign up to set email alerts
|

Opto-Mechanical Eye Models, a Review on Human Vision Applications and Perspectives for Use in Industry

Abstract: The purpose of this review is to aggregate technical information on existent optomechanical eye models (OME) described in the literature, for image quality assessment in different applications. Several physical eye models have been reviewed from peer-reviewed papers and patent applications. A typical eye model includes an artificial cornea, an intraocular lens or other lens to simulate the crystalline lens, an aperture as the pupil, and a posterior retinal surface, which may be connected to a light sensor. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…Phantom eyes (PEs) have been designed for decades 9 , and they are mainly employed in ophthalmic training or to calibrate, design, and evaluate the reliability of ophthalmoscopy devices [10][11][12][13][14][15] . In particular, PEs are made of synthetic (often plastic) materials and enable to emulate: (1) the anterior chamber 16 , (2) the reflectivity and thickness of the retina including the fovea 17,18 , (3) the optic nerve cup and nerve fiber layers 10,13 , and (4) the retinal detachment and dry age macular degeneration 19 .…”
mentioning
confidence: 99%
“…Phantom eyes (PEs) have been designed for decades 9 , and they are mainly employed in ophthalmic training or to calibrate, design, and evaluate the reliability of ophthalmoscopy devices [10][11][12][13][14][15] . In particular, PEs are made of synthetic (often plastic) materials and enable to emulate: (1) the anterior chamber 16 , (2) the reflectivity and thickness of the retina including the fovea 17,18 , (3) the optic nerve cup and nerve fiber layers 10,13 , and (4) the retinal detachment and dry age macular degeneration 19 .…”
mentioning
confidence: 99%
“…The design follows the Gullstrand principle, whereby the beam paths of the sensor and illumination run through different areas of the eye [8]. Studies by other researchers have shown that a suitable arrangement of the illumination means that the Purkinje reflexes of the eye have no disturbing effects on the fundus sensor [12,13]. For the setup shown here, it was found that the Purkinje reflexes have no disturbing effect if the illumination on the lens does not fall below a radius of 2 mm and the fundus system is correctly focused.…”
Section: Near Infrared Lightingmentioning
confidence: 99%